Foot Steps of the Ancient Great Glacier of North America : A Long Lost Document of a Revolution in 19th Century Geological Theory - Borns, Jr., Harold W.; Maasch, Kirk Allen (Springer International Publishing : Imprint: Springer, 2015)
Dr. John K. DeLaski practiced medicine in the Penobscot Bay region of Maine and, in addition, was a naturalist with keen powers of observation. His study of the landscape led to his conclusion that a thick glacier had overtopped the highest hills, filled all of Penobscot Bay, extended far to the east and west and probably was part of a greater continental glacier. He published these observations and inferences in numerous local newspapers and magazines, as well as the American Journal of Science. His work put him on the "team" of Benjamin Silliman, James D. Dana and Louis Agassiz, all advocates for glaciation as the regional land shaping force as opposed to that of the Biblical Deluge, a major scientific conflict of the day both in North America and Europe. Agassiz and other prominent naturalists incorporated DeLaski's observations into their own presentations, often without giving him credit. Published now for the first time, DeLaski's summary work presents a holistic discussion of the controversy in which he presents his critical observations of surficial geology in Maine, southern New England and New Brunswick, Canada and concludes that these depositional and erosional features must be of glacial origin. All this was done while most "naturalists" still advocated the Biblical Flood to explain the major components of surficial geology in North America and abroad.